The Surgical Treatment for Portal Hypertension: A Systematic Review and Meta-Analysis. (27th January 2013) - Yin, Lanning; Liu, Haipeng; Zhang, Youcheng; Rong, Wen
Abstract : Aim . To compare the effectiveness of surgical procedures (selective or nonselective shunt, devascularization, and combined shunt and devascularization) in preventing recurrent variceal bleeding and other complications in patients with portal hypertension. Methods . A systematic literature search of the Medline and Cochrane Library databases was carried out, and a meta-analysis was conducted according to the guidelines of the Quality of Reporting Meta-Analyses (QUOROM) statement. Results . There were a significantly higher reduction in rebleeding, yet a significantly more common encephalopathy (P = 0.05 ) in patients who underwent the shunt procedure compared with patients who had only a devascularization procedure. Further, there were no significant differences in rebleeding, late mortality, and encephalopathy between selective versus non-selective shunt. Next, the decrease of portal vein pressure, portal vein diameter, and free portal pressure in patients who underwent combined treatment with shunt and devascularization was more pronounced compared with patients who were treated with devascularization alone (P < 0.05 ). Conclusions . This meta-analysis shows clinical advantages of combined shunt and devascularization over devascularization in the prevention of recurrent variceal bleeding and other complications in patients with portal hypertension.